Chemoradiotherapy Is Inferior to Chemotherapy Alone in Adjuvant Setting for Signet Ring Cell Containing Gastric Cancer - Zhu, Yue-Ting; Chen, Xin-Zu; Chen, Ye; Zhou, Yu-Wen; Tang, Lian-Sha; Luo, De-Yun; Li, Qiu; Qiu, Meng; Wang, Xin; Cao, Dan; Yang, Yu; Shen, Ya-Li; et al. (Frontiers in Oncology, 2020)
Background: Signet ring cell containing gastric cancer (SRCGC) is a rare subtype of gastric cancer, and its adjuvant therapy is based on general gastric cancer for the lacking of sufficient evidence. However, the effectiveness of radiotherapy for those SRCGC patients remains unknown. Purpose: The purpose of the study was to analyze whether the addition of radiotherapy to adjuvant chemotherapy (CT) can benefit survival in resected SRCGC patients. Methods: Patients with SRCGC, who underwent D2 gastrectomy followed by adjuvant chemotherapy or chemoradiotherapy (CRT), were retrospectively collected. According to the proportion of signet ring cell, patients were histologically classified as, pure SRCGC (pSRCGC) containing 100 % of signet ring cells, mixed SRCGC (mSRCGC) containing >50 % of signet ring cells, and contaminated SRCGC (cSRCGC) containing <50 % of signet ring cells. Among the 272 patients, 156 were treated by CT alone and 116 by CRT. The primary endpoint was 3-year overall survival rate (3-year OS rate). Results: With a median follow-up of 80.5 months, the 3-year OS rate was significantly higher in the CT group (70.5 % vs. 58.6 %, HR = 0.633, P = 0.017) compared with CRT group. Three independent characteristics were predictive of a poor overall survival: CRT treatment (P = 0.019), tumor size ≥5cm (P < 0.001), and the presence of vessel invasion (P = 0.009). Subgroup analyses showed CRT significantly impair prognosis in SRCGC patients with cSRCGC subset, as well as lesions located in lower-middle sites, subtotal gastrectomy, male, < 60 year, and no vessel invasion. Peritoneal was the most common recurrence site in SRCGC patients. Adverse events leukopenia and neutropenia were more common in CRT group (P = 0.007). Conclusions: Adjuvant chemoradiotherapy was associated with poor survival compared with adjuvant chemotherapy in SRCGC patients with D2 gastrectomy.